PEMANFAATAN SAMPAH ORGANIK UNTUK PEMBUATAN KOMPOS SEBAGAI PUPUK PERTANIAN DAN BUDIDAYA ULAT MAGGOT SEBAGAI PAKAN TERNAK DI DESA PRINGGAJURANG - Hambali, Alfan Hambali; Irnawati, Diah Harun; Ningsih, Fina Dwi; Pratama, Jihan; Karmelia, Mala; Sukma, Rojina; Putra, Syafaren Arjuna; Irfansyah, Taufik Nur; Aprilia, Winda Sari (Universitas Mataram, 2024)
Pringgajurang Village is a village located in Montong Gading District, East Lombok. The majority of people living in Prerang Village work as farmers and livestock breeders. Pringgajaurang village has an area of ​​around 265.89 hectares. After that, when the BSF fly eggs hatch, they are left to become prepupae which will then be fed with organic waste and then left with a lid for 2 weeks. After that, the bucket containing the prepupae is moved into the BSF fly net. first and fed organic waste..To begin with, it is best to let the prepupa become BSF flies first so that they produce more eggs which will later be made into maggots for use as feed..Cultivating BSF flies is a way to cultivate maggot caterpillars, because these BSF flies will die After mating and laying eggs, it is best not to turn them into maggots first, but half of them to become BSF flies again. Metamorphosis of BSF flies starts from mating, 2-3 days later the male will die and the female will lay eggs and then die too after laying eggs. The eggs will hatch 3 to 4 days later. become larvae, then become adult larvae, then become prepupa, and then become blackish and end up becoming BSF flies